PERAN RUANG TERBUKA HIJAU DALAM MITIGASI PERUBAHAN IKLIM - SOSIALISASI DAN PELATIHAN BAGI AMGPM DI DESA LATUHALAT KOTA AMBON - Pietersz, Juglans Howard; Mustamu, Sofia; Kewilaa, Viktor L. N. (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Green open spaces (RTH) are public areas that play a strategic role in climate change itigation, particularly as CO2 absorbers and O2 producers, microclimate regulators, urban pollution reducers, and creators of thermal comfort for urban communities. However, the lack of knowledge and awareness among the public has led to the neglect of RTH existence. People remain trapped in improper RTH waste management practices, contributing to greenhouse gas emissions that exacerbate global warming. This community service activity is an educational effort aimed at enhancing public knowledge, improving skills, and correcting improper RTH management practices. The activities include socialization on the role of RTH in climate change mitigation, training on RTH waste management, and a collective tree-planting initiative. The series of activities is expected to raise public awareness about the importance of maintaining and protecting RTH as a safeguard in climate change mitigation. Additionally, it aims to foster collective actions within the community to contribute to saving the planet.